A Survey on General Pharmacology and Adverse Drug Effects among Undergraduate Medical Students: A Descriptive Study (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Pharmacology is one of the cornerstones of the drug discovery process. It has been defined as “an experimental science which has for its purpose, the study of changes brought about in living organisms by chemically acting substances (with the exception of foods), whether used for therapeutic purposes or not.” The purpose of this study was to assess the knowledge on general pharmacology and adverse drug effects.MATERIALS AND METHODS: This cross-sectional study was conducted at Janaki Medical College from January 2021 to February 2021 among MBBS First and second year undergraduate students. A structured quantitative survey, was used as an instrument for data collection. A total of 120 participants completed the questionnaire. Data analysis was carried out using SPSS version 21.0 software.RESULTS: In the current study, out of 120 undergraduate MBBS students, 67.5% were males and 32.5% were females. The main purpose of using drug was for treatment as reported by 33.3% of the respondents, major source of drug was plants (69.2%), while generic name was the most commonly remembered drug nomenclature. Oral route was the most common route (100%) as well as the most preferred (89.2%) route of drug administration. The first line of treatment for any illness was home remedies (54.2%) while 69.2% of the respondents reported to consume drugs for any illness after prescription by a registered medical practitioner. Similarly, 80.8% of the respondents took drugs in adequate dose while 83.3% reported to take drugs for adequate period of time for any illness. Type A was the most commonly (79.2%) reported adverse effects.CONCLUSIONS: The study findings demonstrated the need to reinforce information on general pharmacology and adverse effects related to different dosage forms of medications to the future practitioners.